Analisis Pengaruh Ketebalan dan Jenis Inti Besi Rotor dan Stator terhadap Karaktersitik Generator Sinkron Magnet Permanen 18S16P Fluks Radial - Raditya Saputra; Zulfatri Aini (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
People's energy needs are always increasing and electricity supply in Indonesia is still dominated by non-renewable energy sources, namely fossil fuels. The use of fossil fuels will be exhausted if exploited continuously. To overcome this problem is to utilize renewable energy sources. Besides being able to reduce the use of fossil fuels, renewable energy can reduce environmental impact. One form of renewable energy source is wind. Wind is able to drive a turbine and generate electricity from a generator. Permanent Magnet Synchronous Generator is a generator that consists of two main components is Rotor and Stator. PMSG is modeled using software with the Finite Element Method (FEM) method. Of course, to get higher characteristics, the generator must have the right material and geometry. This research varied the thickness and types of iron cores in the rotor and stator to be able to produce an output power value of 1000 watts / 1 kW. This current value is used to get the value; voltage, torque, input power, output power and efficiency. The variation of the thickness of the rotor and stator iron core is at 37 mm, 52 mm and 80 mm and for the type of iron core the materials used are M1000-100A and Carpenter: Silicon Steel. Carpenter iron core type: Silicon Steel. The biggest current and voltage are produced by Carpenter's core type: Silicon Steel with 80 mm thickness with a value of 17.44 A and 52.31 V.